Language Laboratories and English Communication in Odisha’s Higher Education: A Comparative Study - Dash, Rakesh kumar (International Journal of Education, Language, and Social Science, 2025)
Although the overall status of English language learning in Odisha is relatively stable, students’ achievement in communication skills varies considerably across educational institutions. This variation is largely attributed to the presence and effective use of language laboratories in the teaching and learning process. Institutions that incorporate language labs into their instructional practices tend to report better student outcomes in communication proficiency, whereas those that do not utilize such facilities show limited progress. This study aims to examine the impact of language labs on university students' English communication skills in Odisha. The research employs a survey method using a structured questionnaire, with data collected from both a private and a public university.The findings reveal that language laboratories play a significant role in enhancing students’ communicative competence when effectively managed. Private universities demonstrate stronger results due to modern equipment, skilled instructors, and regular use of the facilities. In contrast, government universities face limitations such as outdated infrastructure, insufficiently trained staff, and a lack of consistent practice sessions. These disparities suggest the need for improved implementation and investment in language lab facilities within public institutions to ensure more equitable language education across the higher education sector in Odisha.